MINI-REVIEW MENGENAI PEMANFAATAN MATERIAL BERBASIS POLIMER KOORDINASI BERPORI UNTUK PENYIMPANAN HIDROGEN - Syaima, Husna; Intifadhah, Sahara Hamas (Jurusan Kimia FMIPA UNMUL, 2023)
This review aims to summarize the various types of Metal-Organic Frameworks (MOFs) and their utilization for hydrogen storage. MOFs have high surface area, flexibility, good stability and tunability, various active sites, and abundant raw materials. These characteristics make MOFs worthy of being considered as a new material in hydrogen storage applications. The potential for using MOFs is very broad because its properties can be determined from the choice of metal and linker. Hydrogen gas storage commonly requires high pressure tanks whereas in liquid form, it requires cryogenic temperatures due to its very low boiling point, the challenge is to synthesize MOF with high hydrogen adsorption capacity under mild conditions. Moreover, it is crucial to learn about the relationship among the pore volume and surface area of MOFs, physisorption of hydrogen, and adsorption condition.